PELAKSANAAN SUPERVISI AKADEMIK DALAM RANGKA PENINGKATAN KINERJA GURU KIMIA DI SMAN 1 TEUNOM ACEH JAYA - Wasmaini Budiarti; Yusrizal .; Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2015)
Abstract: Academic supervision carried out due to low student achievement in the study of chemistry, as a result of poor performance and lack of chemistry teacher motivation and guidance of the principal. Important academic supervision to be carried out by the principal of SMAN 1 Teunom to be able to improve the performance of a chemistry teacher who will have an impact on increasing student learning outcomes in the study of chemistry. The approach used in this study is a qualitative approach with descriptive methods. Data collection techniques are interviews, documentation and observation. Subjects were headmaster and chemistry teacher. Based on the results of the study showed that: (1). Academic supervision program designed by the principal based on the needs of a chemistry teacher, improve the situation of learning, curriculum development and evaluation (2). Supervision techniques used are individualized supervision techniques, namely classroom visits, classroom observations and personal conversations, as well as engineering group, namely the meeting during the board meeting of teachers, (3). Follow-up of academic supervision, namely the implementation of learning workshops, clinical supervision and subject teachers conduct discussions. Conclusion: The program provides academic supervision of activities designed to help chemistry teachers to improve their performance, academic supervision techniques are used to directly observe the appearance and abilities of teachers, as well as activities and student learning directly, follow-up carried out in three ways, namely guidance to teachers either directly and indirectly, strengthening supervision and reporting of the results of the instruments academic supervision. Keywords: Academic Supervision and Teacher PerformanceAbstrak: Supervisi akademik dilaksanakan karena rendahnya prestasi belajar siswa pada bidang studi kimia, yang diakibatkan dari rendahnya kinerja guru kimia serta kurangnya pemberian motivasi dan bimbingan dari kepala sekolah. Supervisi akademik penting untuk dilaksanakan oleh kepala sekolah SMAN 1 Teunom untuk dapat meningkatkan kinerja dari guru kimia yang akan berdampak pada meningkatnya hasil belajar siswa pada bidang studi kimia. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data adalah wawancara, dokumentasi dan observasi. Subjek penelitian adalah kepala sekolah dan guru kimia. Berdasarkan hasil penelitian menunjukkan bahwa: (1).Program supervisi akademik dirancang oleh kepala sekolah berdasarkan kebutuhan guru kimia. memperbaiki situasi pembelajaran, pengembangan kurikulum serta evaluasi, (2).Teknik supervisi yang digunakan adalah teknik supervisi individual, yaitu kunjungan kelas, observasi kelas dan percakapan pribadi, serta teknik kelompok, yaitu pertemuan pada saat rapat dewan guru, (3). Tindak lanjut supervisi akademik, yaitu workshop pelaksanaan pembelajaran, supervisi klinis dan kegiatan MGMP. Kesimpulan: Program supervisi akademik berisi rancangan kegiatan untuk membantu guru kimia meningkatkan kinerjanya, teknik supervisi akademik digunakan untuk melihat langsung penampilan dan kemampuan guru, serta aktivitas dan cara belajar siswa secara langsung, tindak lanjut dilaksanakan dengan tiga cara, yaitu pembinaan terhadap guru baik secara langsung dan tidak langsung, pemantapan instrumen supervisi dan pelaporan hasil supervisi akademik. Kata kunci: Supervisi Akademik dan Kinerja Guru